DAMPAK KEGIATAN RUTIN BERBAGI TERHADAP PENGEMBANGAN KARAKTER SISWA KELAS V SD NEGERI 80 PALEMBANG - Laeli, Dian Shofariatu; Murjainah, Murjainah; Oktavia, Maharani (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to determine the impact of routine sharing activities on the character development of fifth-grade students at SD Negeri 80 Palembang. The research uses a descriptive qualitative approach, with instruments including observation, interviews, questionnaires, and documentation. The study was conducted from July to August 2024, with the subjects being 26 students from class VA and one teacher or class supervisor at SDN 80 Palembang. Based on the results of the observations and student questionnaire responses, character development in the five indicators assessed was found to be good. This indicates that the routine sharing activities carried out by students have a positive impact on their character development, particularly in values such as love for peace, communication, social awareness, tolerance, and willingness to sacrifice. The questionnaire results from the 26 students show that, on average, students chose the responses